2020
DOI: 10.1016/j.annonc.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of chemotherapy and atezolizumab in patients with non-small-cell lung cancer receiving antibiotics and proton pump inhibitors: pooled post hoc analyses of the OAK and POPLAR trials

Abstract: Background: Preclinical data have shown that proton pump inhibitors (PPI) can modulate the microbiome, and singlearm studies suggested that antibiotics (ATB) may decrease the efficacy of immune checkpoint inhibitors (ICI), but randomized controlled trial data are lacking. This pooled analysis evaluated the effect of ATB and PPI on outcome in patients randomized between ICI and chemotherapy. Patients and methods: This retrospective analysis used pooled data from the phase II POPLAR (NCT01903993) and phase III O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
243
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(258 citation statements)
references
References 24 publications
14
243
0
1
Order By: Relevance
“…This observation was not found for the docetaxel arms. 25 Similar data were also observed for other cancer types like renal cell carcinoma. 26 This phenomenon could be explained by the role of the microbiota.…”
Section: Medicationsupporting
confidence: 75%
“…This observation was not found for the docetaxel arms. 25 Similar data were also observed for other cancer types like renal cell carcinoma. 26 This phenomenon could be explained by the role of the microbiota.…”
Section: Medicationsupporting
confidence: 75%
“…6 7 In the case of systemic antibiotics, the evidence for a causative effect seems stronger and more plausible in view of their capacity to perturbate the gut microbiome, a renown determinant of response to ICIs. [8][9][10] Nevertheless, the risk of collinearity with the underlying cause for the antibiotics prescription (eg, infections which might subtend to poorer clinical condition), has yet to be fully discriminated.…”
Section: Open Accessmentioning
confidence: 99%
“…Proton pump inhibitors were associated to decreased progression-free survival (PFS) and overall survival (OS) in non-small-cell-lung-cancer (NSCLC) and melanoma patients receiving programmed death-1 (PD-1)/programmed death ligand-1 (PD-L1) checkpoint inhibitors, 9 11 while some studies investigated the impact of other concomitant medication, such as non-steroidal anti-inflammatory drugs (NSAIDs), metformin, aspirin, β-blockers and statins, without conclusive results. 12 13 …”
Section: Introductionmentioning
confidence: 99%
“…The composition and the diversification of the gut microbiota play an important role in the response to ICI as shown by Frankel et al, who reported that patients who had Bacteroidescaccae in their gut flora had better responses to ICI [ 264 ]. The use of antibiotics 30 to 60 days prior to treatment with ICI and the use of PPI have been shown to have a deleterious effect on ICI efficacy, as reported by Chalabi et al [ 265 ], and this may be due to the decrease in the diversity of bacterial species and an increase gastric pH, which affects gut microbiomes [ 266 , 267 ]. The gut microbiota and its role in ICI resistance is still not clearly understood, and further studies are needed to further clarify its role.…”
Section: Mechanisms Of Resistance To Immunotherapy and Ways To Ovementioning
confidence: 99%